2020
DOI: 10.1093/ajhp/zxaa251
|View full text |Cite
|
Sign up to set email alerts
|

Medication utilization in patients in New York hospitals during the COVID-19 pandemic

Abstract: Disclaimer In an effort to expedite the publication of articles related to the COVID-19 pandemic, AJHP is posting these manuscripts online as soon as possible after acceptance. Accepted manuscripts have been peer-reviewed and copyedited, but are posted online before technical formatting and author proofing. These manuscripts are not the final version of record and will be replaced with the final article (formatted per AJHP style and proofed by the authors) at a later time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“… 4 , 5 , 9 A study in New York hospitals found sharp increases in aggregate utilization of sedative and analgesic medications during the early weeks of the COVID-19 pandemic, consistent with the surge in patient numbers, but the study did not examine individual patient dosing. 10 Our study was the largest study to systematically quantify individual sedation and analgesic dosing requirements for mechanically ventilated, critically ill patients with COVID-19 that has been conducted to date (as of the time of writing). High analgesic and sedative medication requirements were observed in a multi-ICU cohort of mechanically ventilated, critically ill patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 , 9 A study in New York hospitals found sharp increases in aggregate utilization of sedative and analgesic medications during the early weeks of the COVID-19 pandemic, consistent with the surge in patient numbers, but the study did not examine individual patient dosing. 10 Our study was the largest study to systematically quantify individual sedation and analgesic dosing requirements for mechanically ventilated, critically ill patients with COVID-19 that has been conducted to date (as of the time of writing). High analgesic and sedative medication requirements were observed in a multi-ICU cohort of mechanically ventilated, critically ill patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Sedatives such as propofol, midazolam, and ketamine have been used in both mechanical ventilation management and PSA. These sedatives, particularly propofol, have been in serious short supply during the pandemic, 8 and might be prioritized for use in mechanical ventilation management. As such, propofol may not be available for PSA in some EDs.…”
Section: Discussionmentioning
confidence: 99%
“…Sedatives such as propofol, midazolam, and ketamine, which are frequently used in PSA, were in serious short supply. 8 …”
Section: Introductionmentioning
confidence: 99%
“…Although most shortages are a result of production interruption, surges in demand for specific drugs during a pandemic can also lead to inadequate supply. 4 In some cases, there were surges in treatments known to be effective in supportive care (eg, albuterol). In other cases, speculation about a drug’s effectiveness led to panic buying and therefore rapidly depleting inventory.…”
Section: National/state/local Preparationmentioning
confidence: 99%